Study of Laterally Stacked Nanostructures Using an Organic Semiconducting Channel Fabricated by Trench Isolation Technique - Ghosh, Joydeep (Institute of Electrical and Electronics Engineers (IEEE), 2020)
10.1109/tnano.2020.2994640